Intracorneal and Intraocular Invasion of Ocular Surface Squamous Neoplasia after Intraocular Surgery: Report of Two Cases and Review of the Literature - Murillo, Juan C. (Ocul Oncol Pathol, 2017)
PURPOSE: The aim of this paper was to describe 2 cases of ocular surface squamous neoplasia (OSSN) of the conjunctiva with intracorneal and intraocular extension following intraocular surgery. METHODS: We conducted a clinical pathological retrospective case series. RESULTS: Case 1 underwent cataract surgery in the setting of an unnoticed adjacent OSSN. An excisional biopsy with cryotherapy and intraoperative mitomycin C was subsequently performed, confirming OSSN. The patient had two recurrences treated topically with resolution. While the conjunctiva remained clear, a corneal haze emanating from the cataract incision site was noted. Penetrating keratoplasty (PK) for this haze revealed midstromal infiltrative carcinoma. Case 2 had a history of herpes simplex keratitis that ultimately required corneal grafts. Fifteen years later, he developed an OSSN treated with excisional biopsy and had clear margins. Eight months later, he presented with a recurrence of his OSSN and was treated briefly with topical interferon for 4 weeks; however, he developed an infectious keratitis with a corneal perforation requiring another PK. Four months after PK, low-grade inflammation was noted. Cytology of the anterior chamber aspirate revealed neoplastic squamous cells. Another PK was then performed. Pathology confirmed extensive intraocular neoplasia. Limited exenteration was performed. CONCLUSION: Patients with a history of OSSN may be at increased risk of neoplastic intraocular extension following intraocular surgery.